Factors That Influence The Decision To Purchase Syar’i Products On Tasikmalaya Centennial (Survey On IAIT Femele Students In Tasikmalaya City) - Amelia Aprilliyani Muttaqin; Budhi Wahyu Fitriadi; Rita Tri Yusnita (Journal of Management, Economic, and Accounting, 2023)
The purpose of this study was to determine the factors that influence the decision to purchase syar'i products for sentennials in Tasikmalaya City. The research method used is the questionnaire method with a survey approach to 100 respondents who are IAIT students who use syar'i products. the types of data used are primary data and secondary data. The data analysis technique used is multiple regression analysis. The results of this study prove that simultaneously cultural, social, personal, and psychological factors have a significant effect on the decision to purchase syar'i products for IAIT Tasikmalaya students. While cultural factors partially do not have a significant effect on purchasing decisions, social factors do not have a significant effect on purchasing decisions, personal factors have a significant effect on purchasing decisions, and psychological factors have a significant effect on purchasing decisions on syar'i products in IAIT Tasikmalaya students.